24-Hour Proteinuria Weakly Correlated with Estimated Glomerular Filtration Rate in Lupus Nephritis Patients - Suhendra Praptama; Yulia Hayatul Aini; Mohammad Ghozali; Laniyati Hamijoyo (Indonesian Journal of Rheumatology, 2016)
Background: Lupus Nephritis (LN) is still the most frequent complication in Systemic Lupus Erythematous (SLE) patients which causing the major and significance morbidity and mortality. Proteinuria and Glomerular Filtration Rate (GFR) serves as objective and routine examinations to assessrenal function. 24-hour proteinuria still regarded as gold standard to quantify amount protein in urine. Estimated GFR (eGFR) is preferably used due its convenient. On the hand, estimated GFR (eGFR) is preferably used due its convenient. However, both of them should be measured in order to determine renal progression and prognosis. Only few studies have been conducted to find out the correlation between 24-hour proteinuria and eGFR in lupus nephritis patients as both of them serve as potential marker in progression of renal involvement. Thisstudy addressed to find out correlation between 24-hour proteinuria and eGFR in lupus nephritis patients.Method: Analytic-correlation study with cross-sectional approach at Dr. Hasan Sadikin Hospital, Bandung was done. Secondary data was used and paralleled with previous study entitled â€œCorrelation of Random Urine Protein Creatinine (P-C) Ratio with 24-Hour Protein Urinein Lupus Nephritis Patientsâ€ carried out from October to December 2014.Correlation coefficient was analyzed by Spearmansâ€™ correlation test.Results: Forty five samples were obtained based on inclusion criteria. Spearmansâ€™ correlation test revealed non significant and very weak correlation between 24-hour proteinuria and eGFR (r=-0.095) with p>0.05.Conclusion: The 24-hour proteinuria and eGFR are weakly correlated. Despite the weakÂ  correlation, these examinationsshould be considered as important markers to monitor prognosis of renal involvement in lupus nephritis patients Keywords: Estimated glomerular filtration rate (eGFR),Lupus Nephritis (LN), Proteinuria, Systemic Lupus Erythematosus (SLE).